Does a combined technical and didactical training program improve the acceptance of student tutors in the dissection course? A prospective controlled randomized study - Shiozawa, Thomas; Hirt, Bernhard; Celebi, Nora; Werner, Anne; Weyrich, Peter; Lammerding-Koeppel, Maria (Annals of anatomy, 2010)
Student tutors in the dissection course are expected to meet high demands on their job. We developed a combined technical and didactical training on the basis of literature review and needs assessment. The three-week training program comprised dissection as well as presentation techniques, group dynamics and activating teaching methods. A randomized, controlled, single-blind study was set up to test whether there is a difference between the tutee's perception of the tutor competences, comparing trained and untrained tutors. A total of 10 trained and 10 untrained tutors (control group) were enlisted in the study. The acceptance of the training program was measured with a questionnaire (11 items, 5-point Likert scale) where the tutees rated the competences of the tutors. The tutees were assigned randomly to their tutor and blinded to his/her training. The tutees assessed the trained tutors better in all categories compared to the untrained tutors. A significantly better score ( p < 0.05) was stated for the categories “conveying basic dissection techniques” (4.31 ± 0.86 vs. 3.89 ± 1.05), “positive group atmosphere” (4.69 ± 0.73 vs. 4.44 ± 0.88), “learning support” (4.24 ± 1.03 vs. 3.79 ± 1.16) and “visualisation” (3.99 ± 1.11 vs. 3.56 ± 1.17). In self-assessment, the trained tutors rated themselves significantly better after the training compared to before in all categories. The specific training curriculum for tutors in the dissection course, focusing on the improvement of content knowledge, technical and didactical competencies, is well accepted by the tutees and tutors.